2008
DOI: 10.1002/jpln.200700048
|View full text |Cite
|
Sign up to set email alerts
|

Organo‐mineral associations in temperate soils: Integrating biology, mineralogy, and organic matter chemistry

Abstract: We summarize progress with respect to (1) different approaches to isolate, extract, and quantify organo‐mineral compounds from soils, (2) types of mineral surfaces and associated interactions, (3) the distribution and function of soil biota at organo‐mineral surfaces, (4) the distribution and content of organo‐mineral associations, and (5) the factors controlling the turnover of organic matter (OM) in organo‐mineral associations from temperate soils. Physical fractionation achieves a rough separation between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
592
6
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,027 publications
(637 citation statements)
references
References 160 publications
31
592
6
8
Order By: Relevance
“…With respect to these low-molecular-weight humic fractions, it has been clearly demonstrated that they can act efficiently as natural substrates for Fe acquisition by roots of monocots and dicots (Pinton et al 1997b(Pinton et al , 1999Cesco et al 2002). HS increase Fe bioavailability through their Fechelating properties and have redox-reactive properties (Kögel-Knabner et al 2008). These properties are related to phenolic groups contributing to Fe III reduction.…”
Section: Soil Organic Carbon Related With Iron Cyclementioning
confidence: 99%
“…With respect to these low-molecular-weight humic fractions, it has been clearly demonstrated that they can act efficiently as natural substrates for Fe acquisition by roots of monocots and dicots (Pinton et al 1997b(Pinton et al , 1999Cesco et al 2002). HS increase Fe bioavailability through their Fechelating properties and have redox-reactive properties (Kögel-Knabner et al 2008). These properties are related to phenolic groups contributing to Fe III reduction.…”
Section: Soil Organic Carbon Related With Iron Cyclementioning
confidence: 99%
“…While the importance of land use and management systems on soil organic carbon pools has received considerable attention (Davidson and Janssens 2006;Ko¨gel-Knabner et al 2008), the role of the soil inorganic carbon pool in global climate change is not well understood (Lal and Kimble 2000). The present findings provide the first time evidence demonstrating that the nature and relative abundance of biomolecules, such as sugars, amino acids and polyphenols, not only have a significant effect on the generation of humic substances, but also on the formation of carbonate, both of which are mechanisms of C sequestration in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…In the environment, the transformation of biomolecules originating from organized structures typical of organisms to randomly polymerized, heterogeneous humic substances characteristic of biogeochem-ical systems is pivotal to humic substance formation and subsequent organic C stabilization (Torn et al 1997;Ko¨gel-Knabner et al 2008). Abundant research evidence at the molecular level shows that mineral colloids, such as metal oxides, layer silicates and natural soil clays, can accelerate abiotic oxidative polymerization and/or polycondensation of biomolecules such as amino acids, sugars, and polyphenols derived from the breakdown of biological residues and from biological metabolites Huang 1982, 1984b;Stevenson 1994;Huang 2000;Clapp et al 2005).…”
mentioning
confidence: 99%
“…This time around, three oral presentations (Georg Guggenberger, Ingrid Kögel-Knabner, Klaus Kaiser) directly addressed different aspects of mineral stabilization of organic matter in soils. Much of the material presented was based on a series of recent publications by this group Kögel-Knabner et al 2008). Furthermore, Johann Six presented evidence that soils have a maximum capacity for C storage which is related to ''saturation'' of mineral association (see: Six et al 2002;Chung et al 2008;Gulde et al 2008;Stewart et al 2008).…”
Section: Conference Highlightsmentioning
confidence: 99%